META-ANALYSIS STUDY OF FACTORS AFFECTING AUDIT DELAY - Amelia Vernanda; Carmel Meiden (Jurnal Scientia, 2023)
This study was conducted to analyze the factors affecting audit delay in 2012-2022. This study produced as many as 825 articles, found data from Publish or Perish (PoP) software, then 269 candidate articles, and produced 50 selected articles that matched the research criteria. Thus, this study integrates the results of research on 50 selected articles to determine the influence of factors that affect audit delay using the meta-analysis study research method. The independent variables studied were solvency, corporate profit and loss, audit committee, and reputation of public accounting firms (KAP). This research uses the foundation of agency theory and signal theory. Based on agency theory, companies that act as principals need an independent auditor who acts as an agent to carry out an audit process on financial statements that have been prepared by the company with the aim of improving the accuracy of company information. Based on signal theory, a signal is an action taken by company management where management is a party who controls the company's internal information and future prospects in detail compared to external parties. The hypothesis formed in this study is that solvency, company profit and loss, audit committee, and PAF reputation have a significant effect on audit delay. Based on the results of the meta-analysis test conducted, it can be concluded that all independent variables studied, namely solvency, company profit and loss, audit committee, and KAP reputation, significantly affect audit delay.